Artikel Ilmiah Sebagai Komponen Pendukung Kenaikan Pangkat Dan Sertifikasi Bagi Guru Mgmp Seni Di Upt Dinas Pendidikan Kecamatan Sambirejo - Ana Rosmiati (Institut Seni Indonesia Surakarta, 2016)
Writing scientific paper is mater that is felt hard the teacher the unit office of Sragen. This recall is a still a lack of facilities, infrastructure, and training that supports the competency of teaches about the written word. Looking at these conditions, the authors fell the need to perform service on the writing of scientific paper to support the promotion and certification for teahers. The aim of the training service to the communities in the form of teacher to be promoted to a higher level. InÂ addition, as one component of certification is to construct a supporter of scientific writing. The method used in community service activities include training menthods, membring menthods, an menthod of forming a forum of scientific assessments. The training menthod is done by givingÂ training to teacher on a regular basic every two works. Menthods of assistance were made to provide reinforcement tho the teacher in preparing scientific paper after training in completed.Â Establishment of a forum of scientific assessments a conducted regularly every month to motivate the teacher in the study of scientific writing. The result of this dedication teacher can more up to clas Iv without difficulty in the preparation of scientific paper and teachers can be certified. Key words : Scientific work, certification, and rank